EXPLORING RELIGIOSITY AND SOCIOECONOMIC STATUS AS PREDICTORS OF ALTRUISM AMONG UNDERGRADUATES IN SOUTHEAST NIGERIA - Okechukwu Okafor, Chiedozie; I. Onuoha, Florence; Chikezie, Chinomso (African Journal of Social and Behavioural Sciences, 2024)
This study investigated the effects of religiosity and socioeconomic status on altruism among undergraduates in Southeast Nigeria. The Social Exchange Theory (Homans, 1958) and Durkheim’s Unified Theoretical Model of Religion (1964) formed the framework of the study. Both theories provide essential frameworks for understanding altruism in the Nigerian context: Social exchange theory highlights the transactional nature of relationships, while Durkheim emphasizes religion’s role in promoting social cohesion and moral behaviour. Two hypotheses were tested. First, religiosity significantly predicts altruism. Second, socioeconomic status significantly predicts altruism. The total number of participants was two hundred and twenty-nine (229), randomly drawn from the undergraduate student population of 3 universities in the Southeast Region of Nigeria. A cross-sectional design was adopted, and multiple regression analysis was used to test the hypotheses. The results revealed that religiosity significantly predicted altruism at the 0.05 significance level and that socioeconomic status did not significantly predict altruism. The study reveals that religiosity significantly predicts altruism in Southeast Nigeria, while socioeconomic status does not, highlighting the strong influence of religious beliefs on helping behaviour. Altruism in this context is driven more by moral and ethical values from religious teachings rather than wealth or material resources. This suggests that initiatives promoting prosocial behaviour may be more effective when aligned with religious motivations rather than economic incentives. The findings encourage further research into how cultural and social factors, such as education and socialization, influence altruistic behaviours.